Therapeutic effect of Prosopis strombulifera (LAM) BENTH aqueous extract on a murine model of cutaneous leishmaniasis - Lozano, Esteban Sebastián (2022)
Background and aim: Prosopis strombulifera (Lam.) Benth is a rhizomatous shrub native from different zones of Argentine Republic. P. strombulifera aqueous extract (PsAE) has different effects and several biological activities have been reported. The goal of this study was to analyze the activity of PsAE on a murine model of cutaneous leishmaniasis caused by Leishmania amazonensis. Experimental procedure: PsAE was orally administered at 150 mg/animal/day on BALB/c mice infected in the right footpad (RFP) with 1 × 105 promastigotes of L. amazonensis. As a chemotherapeutic control of treatment, animals receive a commercial form of meglumine antimoniate (MA) (Glucantime®, Aventis, Paris, France). Results and conclusion: We observe that the size of RFP lesions of infected mice without treatment showed a grade of inflammation, ulceration and necrosis at the site of infection much greater than that observed with PsAE or MA treatment. Moreover, PsAE was capable of decreasing parasite burden and splenic index. Furthermore, PsAE treated mice showed a significant decrease in O.D. of total anti-Leishmania IgG antibody responses against L. amazonensis. This decrease was similar to those observed when the reference drug, MA, was used. This would indicate that PsAE treatment inhibits or delays disease progression in mice. In conclusion, our findings suggest that PsAE could be a potential candidate to be used, as a new therapeutic strategy, to treat cutaneous leishmaniasis caused by L. amazonensis.